Determination of Isolated Lesion of the Lateral Pectoral Nerve due to Repeated Trauma - Faik Budak; Buket Özkara; Emre Aydin (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
We present two cases of progressive isolated damage to the lateral branch of the pectoral nerve with marked atrophy of the clavicular portion of the major pectoral muscle. In our patients, the mechanism of isolated lesions of lateral pectoral nerves have been attributed to repetitive external microtraumas and pressure on the nerve trajectory between the chest and shoulder during sports or occupational activities. With this case report, we aimed to consider that repetitive microtraumas can cause isolated nerve damage.